Gastrointestinal symptoms in patients with Diabetes mellitus: An integrative literature review (Research, Society and Development, 2025)
Objectives: Obtain information from scientific literature regarding the presence of digestive symptoms in diabetic patients and prevention measures for a common complication. Methodology: This review was conducted in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Inclusion criteria included studies that analyzed the association between Diabetes Mellitus and gastrointestinal symptoms, published between 2011 and 2023 in the bibliographic databases Biblioteca Virtual em Saúde, LILACS, PUBMed and Scielo. Descriptors included “Diabetes mellitus,” “Gastrointestinal Tract,” “Gastrointestinal microbiome,” “Diabetes complications,” “glycemic control,” “hyperglycemia,” and “Diabetes mellitus”; “Gastrointestinal Tract”; “Gastrointestinal microbiome”; “Diabetes complications”; “glycemic control”; “hyperglycemia.” Results: After removing abstracts based on the inclusion and exclusion criteria, we obtained 20 articles eligible for inclusion in this review. Conclusions: The systematic review indicates that gastrointestinal complications are common and frequently underestimated in patients with diabetes mellitus, negatively impacting quality of life. Strict blood glucose control is essential to avoid these complications. More studies are needed on the role of the intestinal microbiome in diabetes and possible therapeutic interventions. Early detection and appropriate management of these complications are crucial to improving patients' prognosis and quality of life.